Körper und Temperaturen: Figurationen des kolonialen Begehrens in der deutschsprachigen Gegenwartsliteratur - Acharya, Swati (Studia Germanica Posnaniensia, 2015)
The central argument of this essay is gathered from two historical novels published around same time and revolving around the same historical figure August Engelhardt. High temperature, in particular the tropical heat finds its metaphorical expression in the sun and then the fever as two prototypical colonial phantasies and/or fears and weaves the narrative around the temperature driven intricacies. Marc Buhls Das Paradies des August Engelhardt (2011) and Christian Krachts Imperium (2012) form the primary sources for the discussion within the topic of colonial desire with reference to the temperature as a significant indicator of either appreciation or devaluation underlining the colonial mentality. My paper concentrates on the overlapping sites within German speaking literature from post-colonial perspective. Along with the works of Marc Buhl and Christian Kracht, I cursorily touch upon Ilija Trojanows novel Der Weltensammler (2006), since it deals with the figure of a historical British colonial officer, Richard Francis Burton. The common thread running through all three works is not only the fact that they deal with scurrile biographies from the pages of colonial history in India and Africa, but that they develop the narrative on another common indicator – the Tropes and their Temperatures.